The India brain infections guidelines project: Global evidence for local application - Priscilla Rupali; Bhagteshwar Singh; Naveena Gracelin Princy; Jisha Sara John; Rebecca Kuehn; Tom Solomon; Hanna Alexander; Prathap Tharyan; G. Singh; Ramasubramanian V; Joseph L. Mathew; Netravathi M; et al. (Elsevier, 2024)
Background: Brain infections are a major cause of morbidity and mortality globally. India lacks systematically evidence-informed guidelines for brain infections. Methods: We had set up a group of experts in brain infections, evidence synthesis and guideline development to produce guidelines for hospital clinicians diagnosing and treating patients with suspected and confirmed brain infections in India. Questions are being drafted and prioritised, and a plan for GRADE-informed evidence synthesis and guideline development is in place, using methods to increase efficiency of the process where possible. Dissemination and outputs: The guidelines will be disseminated through publication as well as on a dedicated website. Training of clinicians in evidence synthesis and guideline development, and setting up a network of institutions and professional societies, will provide lasting impact in terms of national capacity strengthening.